2013
DOI: 10.1017/s0021932013000655
|View full text |Cite
|
Sign up to set email alerts
|

Does Knowledge About Antiretroviral Therapy and Mother-to-Child Transmission Affect the Relationships Between Hiv Status and Fertility Preferences and Contraceptive Use? New Evidence From Nigeria and Zambia

Abstract: The increasing availability of antiretroviral therapy (ART) and drug regimens to prevent mother-to-child transmission (PMTCT) has probably changed the context of childbearing for people living with HIV. Using data from 2009-2010 community-based surveys in Nigeria and Zambia, this study explores whether women's knowledge about ART and PMTCT influences the relationship between HIV status and fertility preferences and contraceptive behaviour. The findings show that women living with HIV are more likely to want mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In our study, nearly two-thirds of the women had shared their HIV status with their partners, and in the multiple regression analysis, women whose partners were aware of their status had almost 6 times higher odds of desiring to conceive in the next 6 months compared with those who had not. This association was not found in Phaweni's study of HIV-positive women recruited from antenatal services in Mpumalanga, South Africa, 40 perhaps because these women had recently given birth. Our findings indicated that disclosure had already occurred among many women interested in conceiving, suggesting that partners could join them directly in pre-conception counseling about safer conception.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, nearly two-thirds of the women had shared their HIV status with their partners, and in the multiple regression analysis, women whose partners were aware of their status had almost 6 times higher odds of desiring to conceive in the next 6 months compared with those who had not. This association was not found in Phaweni's study of HIV-positive women recruited from antenatal services in Mpumalanga, South Africa, 40 perhaps because these women had recently given birth. Our findings indicated that disclosure had already occurred among many women interested in conceiving, suggesting that partners could join them directly in pre-conception counseling about safer conception.…”
Section: Discussionmentioning
confidence: 81%
“…Previous research suggests that determinants of pregnancy intent among HIV-positive persons include personal characteristics and circumstances (younger age of mother, 29 , 33 , 34 being male 13 ); longer time living with HIV/AIDS 21 , 34 , 35 ; better perceived and actual health status 16 , 21 ; being on ARVs 36 ; knowledge (eg, of preventing vertical transmission and ARVs) 12 , 33 , 37 ; reproductive factors (fewer biological children 16 , 21 , 34 , 38 , 39 ); interpersonal and social factors (non-disclosure of HIV status to partner 16 , 21 , 34 ); and geographical factors (by country). 40 However, in the literature to date, there is limited comparison of gender differences in fertility intent and of the factors that lead newly diagnosed HIV-positive individuals to desire children in the immediate future. Among HIV-positive persons who do not use condoms consistently, it is unclear how many do so because of fertility desires.…”
Section: Introductionmentioning
confidence: 99%
“…HIV positive mother on the antiretroviral drug will be with the low viral load so that there is less probability of transmitting to the child through pregnancy, childbirth, and breastfeeding. Mother on chronic HIV care would be with better knowledge of PMTCT and adhered to the recommended prevention mechanism [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Desired fertility is of course a culturally-specific construct. Again using data from the HIV and Achieving Fertility Desires project, Bankole et al (2014b) found that women with HIV in Nigeria were more likely to want more children than were women with HIV in Zambia.…”
Section: Introductionmentioning
confidence: 99%